Pengaruh Efektifitas Penerapan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Pada Kantor Wilayah Kementerian Agama Provinsi Riau - Nelaz, Yolanda Saftri; Nurhasanah, Dinna (Journal of Hospital Administration and Management (JHAM), 2024)
This research aims to find out whether the implementation of government accounting standards has an effect on the effectiveness of the quality of financial reports at the Regional Office of the Ministry of Religion, Riau Province. The data analysis method used is simple linear regression analysis with the help of the SPSS program. The results of research that has been carried out regarding the effect of the effectiveness of implementing government accounting standards on the quality of government financial reports show that Tcount is 33.968 with a significance value of 0.021<0.05 and the results of the regression test show a coefficient value of 0.930 indicating that the variable is the effectiveness of implementing government accounting standards on the quality of government financial reports. positive and significant influence on the quality of government financial reports.